Metabolic response to provision of mixed protein-carbohydrate supplementation during endurance exercise - Miller, S. L.; Maresh, C. M.; Armstrong, L. E.; Ebbeling, C. B.; Lennon, S.; Rodriguez, N. R. (International Journal of Sport Nutrition and Exercise Metabolism, 2002)
The interaction of substrates and hormones in response to ingestion of intact proteins during endurance exercise is unknown. This study characterized substrate and hormone responses to supplementation during endurance exercise. Nine male runners participated in 3 trials in which a non-fat (MILK), carbohydrate (CHO), or placebo (PLA) drink was consumed during a 2-hour treadmill run at 65% VáO2max. Circulating levels of insulin, glucagon, epinephrine, norepinephrine, growth hormone, testosterone, and cortisol were measured. Plasma substrates included glucose, lactate, free fatty acids, and select amino acids. Except for insulin and cortisol, hormones increased with exercise. While post-exercise insulin concentrations declined similarly in all 3 trials, the glucagon increase was greatest following MILK consumption. CHO blunted the post-exercise increase in growth hormone compared to levels in MILK. Free fatty acids and plasma amino acids also were responsive to nutritional supplementation with both CHO and MILK attenuating the rise in free fatty acids compared to the increase observed in PLA. Correspondingly, respiratory exchange ratio increased during CHO. Essential amino acids increased significantly only after MILK and were either unchanged or decreased in CHO. PLA was characterized by a decrease in branched-chain amino acid concentrations. Modest nutritional supplementation in this study altered the endocrine response as well as substrate availability and utilization following and during an endurance run, respectively.